Search for new physics in top quark production in dilepton final states in proton-proton collisions at √s=13TeV - KAYA, MİTHAT (My University, 2019)
© 2019, CERN for the benefit of the CMS collaboration.A search for new physics in top quark production is performed in proton-proton collisions at 13TeV. The data set corresponds to an integrated luminosity of 35.9fb-1 collected in 2016 with the CMS detector. Events with two opposite-sign isolated leptons (electrons or muons), and b quark jets in the final state are selected. The search is sensitive to new physics in top quark pair production and in single top quark production in association with a W boson. No significant deviation from the standard model expectation is observed. Results are interpreted in the framework of effective field theory and constraints on the relevant effective couplings are set, one at a time, using a dedicated multivariate analysis. This analysis differs from previous searches for new physics in the top quark sector by explicitly separating t W from t t ¯ events and exploiting the specific sensitivity of the t W process to new physics.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)